Mechanistic considerations of enantiorecognition on novel Cinchona alkaloid-based zwitterionic chiral stationary phases from the aspect of the separation of trans-paroxetine enantiomers as model compounds - Grecsó Nóra; Kohout Michal; Carotti Andrea; Sardella Roccaldo; Natalini Benedetto; Péter Antal; Ilisz István (2016)
The enantiomers of trans-paroxetine were separated on four chiral stationary phases (CSPs) based on chiral zwitterionic Cinchona alkaloids fused with (R,R)- or (S,S)-trans-2-aminocyclohexanesulfonic acid. The enantioseparations were carried out in polar-ionic or in hydro-organic mobile phases with MeOH/THF, MeCN/THF, MeCN/THF/H2O and MeOH/MeCN/THF containing organic acid and base additives, in the temperature range 0-50 °C. The effects of the mobile phase composition, the natures and concentrations of the additives and temperature on the separations were investigated. Thermodynamic parameters were calculated from plots of ln α vs 1/T. δ(δH°) ranged between -3.0 and +1.5 kJ mol-1, and δ(δS°) between -8.8 and +5.9 J mol-1 K-1. The enantioseparation was generally enthalpically controlled, the retention factor and separation factor decreasing with increasing temperature, but entropically controlled separation was also observed. The elution sequences of the paroxetine enantiomers on the two pairs of pseudo-enantiomeric CSPs were investigated, and an attempt was made to explain the observed anomalies in silico in order to gain an insight into the underlying molecular recognition events between the four chiral selectors and the analyte enantiomers. © 2016 Elsevier B.V.